Measurement of the Jet Mass Distribution and Top Quark Mass in Hadronic Decays of Boosted Top Quarks in pp Collisions at root s=13 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2020)
A measurement is reported of the jet mass distribution in hadronic decays of boosted top quarks produced in pp collisions at root s = 13 TeV. The data were collected with the CMS detector at the LHC and correspond to an integrated luminosity of 35.9 fb(-1). The measurement is performed in the lepton + jets channel of t (t) over bar events, where the lepton is an electron or muon. The products of the hadronic top quark decay t -> bW -> bq (q) over bar' are reconstructed as a single jet with transverse momentum larger than 400 GeV. The t (t) over bar cross section as a function of the jet mass is unfolded at the particle level and used to extract a value of the top quark mass of 172.6 +/- 2.5 GeV. A novel jet reconstruction technique is used for the first time at the LHC, which improves the precision by a factor of 3 relative to an earlier measurement. This highlights the potential of measurements using boosted top quarks, where the new technique will enable future precision measurements.